IDENTIFYING STUDENTS UNDERSTANDING THROUGH PROBLEM POSING - Nasution, Nur Baiti (Jurnal Pendidikan Matematika Undiksha, 2021)
It is obvious that pre service mathematics teacher should have comprehensive understanding in any mathematics for school concept, including linear and quadratic function. The aim of this article is to describe a classroom activity using problem posing model that can be used as a way to identify studentsÂ  understading about linear and quadratic function. Moreover, we also discussed about misconceptions found in the process. This research involved as many as 27 students. The data were collected using observation and documentation of students answer sheets. The data were analyzed qualitatively. The results show that there are students who have misconceptions about the definition of the function and about some terms that often appear in the learning.